Fixed-time artificial insemination with estradiol and progesterone for Bos indicus cows I: Basis for development of protocols - Meneghetti, M. [UNESP]; Sa Filho, O. G. [UNESP]; Peres, R. F. G. [UNESP]; Lamb, G. C.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2009)
Five experiments were conducted on commercial farms in Brazil aiming to develop a fixed-time artificial insemination (TAI) protocol that achieved pregnancy rates between 40% and 55% in Bos indicus cows. These studies resulted in the development of the following protocol: insertion of all intravaginal device containing 1.9 g of progesterone (CIDR) plus 2.0 mg im estradiol benzoate on Day 0; 12.5 mg im dinoprost tromethamine on Day 7 in cycling cows or oil Day 9 in anestrous cows; CIDR withdrawal plus 0.5 mg im estradiol cypionate plus temporary calf removal on Day 9; TAI (48 h after CIDR withdrawal) plus reuniting of calves with their dams on Day 11. Reduced dose of prostaglandin F(2 alpha) (PGF(2 alpha): 12.5 mg im dinoprost tromethamine) effectively caused luteolysis. In cycling cows, fertility was greater when the treatment with PGF(2 alpha) was administered on Day 7 than oil Day 9, but in anestrous cows, no effects of time of the PGF(2 alpha) treatment were found. Estradiol cypionate effectively replaced estradiol benzoate or gonadotropin-releasing hormone as the ovulatory stimulus, reducing labor and cost. In this protocol, CIDR inserts were successfully used four times (9 d each use) with no detrimental effects on fertility. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bos indicus; Estradiol; Fixed-time artificial insemination; Pregnancy rated; Progesterone